Diskrepansi Putusan Hakim dan Tuntutan Jaksa atas Perampasan Aset Penggelapan dalam Jabatan Perspektif Ralf Dahrendorf: Penelitian - Gelora Butarbutar; Agusmidah; Rosmalinda (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Asset confiscation serves as an instrument of social control to eliminate unlawfully obtained profits while simultaneously redressing institutional losses. However, in practice, significant discrepancies often arise between prosecutors' demands and judges' decisions. In a number of decisions, prosecutors consider that the evidence linking assets to the crime has not been met and therefore demand that the assets be returned to the defendant, while judges use judicial discretion to confiscate and return the assets to the victim, based on considerations not fully revealed in the formal evidentiary process. Conversely, there are also cases where prosecutors demand confiscation of assets because they are considered the proceeds or means of a crime, but judges decide differently, rejecting the confiscation because they consider that there is insufficient evidence or a strong causal relationship between the assets and the crime charged. Through a sociology of law approach and jurisprudential analysis, this study finds that this discrepancy is a manifestation of a conflict of authority between two centers of authority in the criminal justice system. The superordinate-subordinate relationship in the structure of the criminal justice system is a manifestation of the conflict of authority between the ...imperatively coordinated associations This creates structural tensions that impact the evidentiary process, the protection of the defendant's rights, and the legitimacy of legal institutions. This conflict also serves as a driver for change through strengthening evidentiary standards and increasing capacity.asset tracing, as well as the urgency of regulatory reform, including mechanismsnon-conviction based forfeitureThis study emphasizes that asset seizure in embezzlement cases must be understood not only through positive legal norms, but also through the social dynamics and distribution of authority that shape judicial practice. Using Ralf Dahrendorf's conflict perspective, this study emphasizes the importance of increasing the transparency of judicial deliberations and the sociological capacity of law enforcement officials to minimize structural tensions between the authority of prosecutors and judges.